Knowledge Sharing of Occupational Safety and Health at Jababeka Industrial Vocational School - Montolalu, Ivan Adrian; Alfaqih, Muhammad Subhan; Nusasenjaya, Radite; Minawati, Minawati (Universitas Syiah Kuala, 2024)
This Community Service activity is motivated by the desire to share knowledge, experiences, and ideas in order to improve understanding and application of Occupational Safety and Health (K3) in the school environment, especially for students of the Jababeka Industry Vocational High School (SMK). The main purpose of this activity is to provide practical insights into the application of K3, both for students, work equipment, and the work environment in schools. This activity involved 42 students from a total of 80 students of SMK Industri Jababeka, consisting of representatives of classes X, XI, and XII. Before the activity is carried out, students take a pre-test to measure their initial understanding. After receiving material in the form of knowledge sharing about K3, students again took a post-test to evaluate the improvement of understanding. The evaluation results showed a significant increase in students' understanding of the concept and application of K3, as reflected in the comparison of pre-test and post-test results. This confirms the effectiveness of the knowledge sharing activities that have been provided. To support efforts to prevent work accidents and occupational diseases, students of SMK Industri Jababeka are expected to continue to improve their knowledge and application of K3 in the school environment. This increased awareness not only protects themselves, but also creates a safe and healthy work culture in the future.